DIFFERENCES OF ASYMMETRIC DIMETHYL ARGININE LEVEL IN PATIENTS WITH DIABETIC NEPHROPATHY AND NON-DIABETIC NEPHROPATHY - Nita Elvina Wisudawati; Coriejati Rita; Leni Lismayanti; Adhi Kristianto Sugianli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Endothelial dysfunction occurs early in Diabetic Nephropathy (DN), characterized by elevated Asymmetric Dimethylarginine (ADMA) levels. Increased ADMA levels may inhibit endothelial Nitric Oxide Synthase (eNOS) production which are required for Nitric Oxide (NO) formation. Decreased NO levels can increase peripheral resistance and exacerbate the endothelial dysfunction. By knowing the difference of ADMA levels in DN and non-DN patients can help the follow-up and management for the progression of endothelial dysfunction. The purpose of this research was to know the difference of ADMA levels in DN and non-DN by a cross-sectional observational analytical method in 53 diabetes mellitus patients at the Dr. Hasan Sadikin Hospital Bandung (December 2016-July 2017). Urine samples were examined to calculate urinary creatinine albumin ratio (uACR) and serum for ADMA levels. Asymetric dimethylarginin was examined by micro ELISA. Most of the subjects were males (60.38%) with the highest age in the range of 55-64 years (45.28%). Increased ADMA levels were found in 100% of DN and 18.5% of non-DN. Median ADMA levels were found in DN 1.01(0.73-2.25) µmol/L and non-DN 0.57(0.27-1.17) µmol/L, showing a significant difference of ADMA levels (p<0.001). High ADMA levels showed endothelial dysfunction in DN. Serum ADMA levels in DN patients were higher than in non-DN.